Analysis Of The Impact Of Employee Engagement On Employee Performance Productivity In The Telkom Bengkulu Area Network Division - Siti Abibah; Ovita Charolina; Amrullah Amrullah (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This research aims to find out and analyze the influence of employee engagement on employee performance productivity in the Telkom Bengkulu Network Division. The type of research used in this research is a quantitative approach. The population in this study is all employees at the Telkom Bengkulu Network Division. The sample used in this study was 70 respondents taken using questionnaire distribution and data analysis techniques. Data analysis used to test hypotheses is simple linear regression analysis and t test (partial test) which is processed using statistical calculation through application (SPSS) version 25. The results of this study show that employee engagement has a positive and significant effect on employee performance productivity in the Telkom Bengkulu Network Division which is evidenced by the regression coefficient value (employee engagement X) of 1,010 and the calculated t value of 7,060 > t table 1,995 with a significant value of 0.000 < 0.05. This means that if employee engagement has a positive and significant effect on employee performance productivity in the Telkom Bengkulu Network Area Division, which shows that when employee performance productivity can regulate the quality of work, with commitment, it can improve the quality of the company